Adapting social protection approaches amid COVID-19 in Bangladesh - Ahmed, Akhter (2020)
Akhter Ahmed POLICY SEMINAR Virtual Event - Social Safety Nets and COVID-19: Can we protect food security and nutrition? Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) JUN 11, 2020 - 09:30 AM TO 10:45 AM EDT